Peran penting satuan pendidikan dalam pengembangan sumber daya manusia di Lamongan - habibah, lailatul (Maliki Interdisciplinary Journal, 2024)
This study aims to explore the important role of educational institutions in the development of human resources (HR) in Lamongan Regency, with a focus on the relationship between education levels and the local economy. Through a literature review approach, this research collects and analyzes data related to the level of education attainment and the economic conditions of the Lamongan community. The findings indicate that higher levels of education are positively correlated with improved HR quality and economic growth. The high level of educational attainment in 2023, reaching 80 %, correlates with a decrease in the number of individuals without diplomas and an increase in job opportunities and social mobility. Recommendations include increasing investment in quality education, integrating curricula relevant to industry needs, and strengthening collaboration between the education and industry sectors. This study provides insights for policymakers to design more effective HR development strategies in Lamongan Regency.